Practicing non-professionals as models for career choices for adult education undergraduates in Nigeria (2016)
Most students studying Adult Education as a discipline in Nigeria’s higher institutions of learning usually ask for the utilitarian value of the course after graduation. This could be because, they initially wanted more popular courses Iike Law, Medicine and Economics and could not gain admission into these disciplines and then found themselves ' studying Adult Education which they probably did not know about before they came to the University. This is why this study teased out knowledge and skill areas of Adult Education and found out from those who have never attended adult education programme either at certificate, diploma or degree levels but has excelled in the identified capacities, skills, training, attitudes and behaviour that the discipline of Adult Education instills in its students. It also identified the unique educational capacities, training skills, functional attitudes, and desirable behaviours that B.Ed. Adult Education programme in University of Ibadan target at producing in its graduates. The study is anchored on value arguments and utilitarianism to prove to doubting categories of students or graduates who found themselves by chance in the department that if those who never had training in Adult Education could make a success of what they are doing, it should be expected that they, who would be professionals of Adult Education should have better opportunities after leaving the University